GOTHIC LINE: MAPPING GOTHIC IN NAPLES. SHARING CULTURE FOR CONSERVATION - Capone, Mara (BDC. Bollettino Del Centro Calza Bini, 2014)
The safeguard actions, to guarantee the conservation and to improve enjoyment of Cultural Heritage, contribute to preserve memory and to promote development of culture. The restriction nature of these actions is not enough to guarantee safeguard of Cultural Heritage, it is necessary that the knowledge is not exclusively aimed to supervision, but it has to communicate the meaning of Cultural Heritage, thus the reason of protection. Our research on a multi-purpose survey of cultural Heritage located in UNESCO Historical Centre of Naples has the following goals: to test communication actions that are able to make aware public of less known Cultural Heritage and to solve the problems connected to disrepair and to management; to design “sustainable enjoyment” systems for Cultural Heritage based on the use of interactive systems available online, in remote or on-site, for different kind of users. Keywords: survey, gothic architecture, ICT for Cultural Heritage